An evaluation of a high school preparatory programme - Du Plessis, Heléne (Institute for Monitoring and Evaluation, 2016)
This dissertation reports a process and outcome evaluation of an anonymised organisation's preparatory programme. The preparatory programme is an out-of-school time (OST) programme that aims to prepare the students that are selected for the scholarship programme, for high school. The programme has been implemented since 2008 and this dissertation will focus on the cohorts which received the programme in 2014 and 2015. The preparatory programme was investigated in terms of its plausibility and a theory of change was developed in consultation with the programme co-ordinator. Three questions related to the programme's process were posed. These questions related to whether the programme had been implemented as intended, whether the CAT instrument that the programme was using was a useful tool for informing selection, and which aspects of the programme the participants found most and least helpful. Five questions regarding outcomes were posed that enquired whether students who had received the programme improved their mathematics and English performance, their cognitive reasoning ability, and their self-efficacy; and whether students in each of the teaching streams had benefitted equally from the intervention. The evaluation used secondary data collected throughout 2015 and included student' term 2 and term 4 report cards, their performance on internal programme assessments, CAT scores, SEQ-C results, a focus group with the teachers who taught on the 2014 iteration of the programme, and interviews with the programme co-coordinator and students that had received the programme. Data analysis methods included the use of descriptive statistics, as well as parametric and non-parametric statistical tests for quantitative data. IBM Statistics 22 was used for the analysis of quantitative data and QSR NV ivo 10 was used for qualitative data. The results revealed that several minor changes were made to the planned structure of the programme in order to maintain the quality of the intervention. Students found the mathematics and English components of the programme useful, although how well they retained and applied the content from the programme varied. Students did not find the creative writing workshops or the study skills workshop particularly useful. The CAT instrument could potentially be a useful tool for informing selection, although it is not currently being used to its full potential. Students' mathematics aggregate s improved significantly, while English aggregates did not. There was no significant change in internal assessment scores for both mathematics and English. Students in the mid-stream appeared to benefit most from the preparatory programme. There was a significant improvement in student CAT scores, as well as on each of the CAT subscales (quantitative, verbal, and non-verbal). There was a significant increase in social self-efficacy scores and a significant decrease in academic self-efficacy scores. Total self-efficacy scores and emotional self-efficacy scores did not change significantly between the pre-and post-test. However, none of these observed effects could be attributed directly to participation in the preparatory programme due to the lack of a comparison group. It is possible that changes between repeated measures on participants were due to maturation effects, regression to the mean, or another historical event which influenced the outcomes of the programme participants.